Bonds of wool: the Pallium and papal power in the Middle Ages - Schoenig, Steven A. (Studies in Medieval and Early Modern Canon Law, 2016)
List of Illustrations; Acknowledgments; List of Abbreviations; Introduction; Part 1: Weaving the Pattern (741-882); 1. Obtaining the Pallium; 2. Bestowing the Pallium; 3. Using the Pallium; 4. Interpreting the Pallium; Part 2: A Well-Worn Garment (882-1046); 5. Carelessness; 6. Creativity; Part 3: The Reformer's Badge (1046-1119); 7. A Tool of the Reform: The Ends; 8. A Tool of the Reform: The Means; 9. New Meanings for a New Age; Epilogue: The Pallium in Classical Medieval Jurisprudence (ca. 1140-ca. 1271); 1. Decretum and Decretists; 2. Decretals and Decretalists; Conclusion